THE EFFECT AND THE UTILIZATION OF X-RAY EXPOSURE AGAINTS MICRONUCLEUS FREQUENCY OF LYMPOCYTES CELLS FOR BIOLOGICAL DOSIMETER - Astari, Triesha Retno; Warih, Agung Pramana (Biotropika: Journal of Tropical Biology, 2015)
ABSTRACT Use of nuclear technology in various fields requires a development of a simple and quick method to determine the risks of person after exposed to radiation. Micronucleus (MN) is one of the indication of structural defect on chromosome as a result of radiation exposure which can be observed in a cell with two nuclei (binucleic cells, BNC), by blocking the cleavage process using cytochalacine-B. The purpose of this study was to determine the frequency of MN that formed after radiation exposure based on gender and age of respondences (donor). Blood samples from six healthy person with age of about 25-51 years old were irradiated with X-ray at doses of 0 and 2 Gy, then MN culturing and its harvesting were done with standard procedures. The results showed that MN frequency was different with differences in age and gender of the respondents ( donors ) that were irradiated at doses of 0 Gy (control) and 2 Gy (α = 5 %). It was found that the MN frequency induced by dose of 2 Gy was significantly higher than that of 0 Gy . However, MN in each age group of 28-30 years, 42-43 years and 50-51 years were not significantly different. It is may be caused by the difference of laboratory condition and other factors such as the amount and sample condition that used with variety of ages >60 years old. The MN test methods of peripheral blood lymphocytes due to radiation enable to be used to learn the irradiation effect in in vitro on the chromosome and can be used as a biological dosimeter.  Key words : Biodosimetri, cytokinesis Block ( CB ), dose, micronuclei, ionizing radiation .